2014
DOI: 10.5455/ijmsph.2014.120920141
|View full text |Cite
|
Sign up to set email alerts
|

Study of cephalic index in Vindhya region of Madhya Pradesh

Abstract: Background: Study of an individual's cephalic length, cephalic breadth and cephalic index is useful in clinical practice, forensic medicine, anthropology and genetic study. It is a useful tool to distinguish race and sex in medico-legal cases. Cephalic index also varies geographically. Aims & Objectives: To study the cephalic index, in Vindhya region of Madhya Pradesh. Materials and Methods: Present study is carried out in the Shyam Shah Medical College and S.G.M. Hospital, Rewa (Madhya Pradesh). For this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Head form prevalence: The results indicated a prevalence of Mesocephalic head form (45.1%) in the Malabar region of Kerala. Concordant results with predominance of mesocephalic head form were observed in the studies of Njemirovskij V et al, 5 Alves HA et al, 6 Nair SK et al, 7 Patro S et al, 8 Mishra M et al, 9 Akinbami BO, 10 Lakshmi KK et al, 11 Shah T et al, 12 Setiya M et al, 13 Ahmed SKN and Sreenivasan M, 14 Ranga MKS and Mallika MCV, 15 Doshi MA and Jadhav SD, 16 Mangeshkar A et al 17 and Thomas MW and Rajan SK. 18 The present study results showed Brachycephalic head form as the second most prevalent group with an incidence of 21% among the study subjects.…”
Section: Discussionsupporting
confidence: 68%
“…Head form prevalence: The results indicated a prevalence of Mesocephalic head form (45.1%) in the Malabar region of Kerala. Concordant results with predominance of mesocephalic head form were observed in the studies of Njemirovskij V et al, 5 Alves HA et al, 6 Nair SK et al, 7 Patro S et al, 8 Mishra M et al, 9 Akinbami BO, 10 Lakshmi KK et al, 11 Shah T et al, 12 Setiya M et al, 13 Ahmed SKN and Sreenivasan M, 14 Ranga MKS and Mallika MCV, 15 Doshi MA and Jadhav SD, 16 Mangeshkar A et al 17 and Thomas MW and Rajan SK. 18 The present study results showed Brachycephalic head form as the second most prevalent group with an incidence of 21% among the study subjects.…”
Section: Discussionsupporting
confidence: 68%
“…We observed the mean CI of the male was 75.59±2.64. This finding was slightly lower than the studies conducted by Singh and Purkit [17] and Mishra et al [18]. Singh and Purkit [17] reported the mean CI of males was 77.71±4.91, and Mishra et al [18] reported 75.84 mean CI in males.…”
Section: Discussionmentioning
confidence: 53%
“…This finding was slightly lower than the studies conducted by Singh and Purkit [17] and Mishra et al [18]. Singh and Purkit [17] reported the mean CI of males was 77.71±4.91, and Mishra et al [18] reported 75.84 mean CI in males. Another Indian study from the Manipal region reported 77.92 mean CI in males [19] and Shah and Jadav [20] reported that CI's value was 80.42 in Gujrati males.…”
Section: Discussionmentioning
confidence: 53%